The role of epidermal differentiation gene complex studies in atopic dermatitis - Özge Gündüz; Deepak Modi; Raquel Duarte (Galenos Publishing House, 2021)
Atopic dermatitis (AD) is a chronic skin disease affecting mainly children with an increasing prevalence worldwide. AD is a complex trait resulting from genetic predisposition, skin barrier dysfunction, immune dysregulation, and environmental factors. The major risk factors for AD are a family history of atopy (eczema, asthma, or allergic rhinitis) and the loss-of-function mutations in the filaggrin (FLG) gene. This review highlights the role of the genetic abnormalities identified in AD, from the susceptibility loci in genome-wide associations to epigenetic studies.